Crop type rather than production method determines functional trait composition of insect communities on arable land in boreal agricultural landscapes - Toivonen, Marjaana; Huusela, Erja; Hyvönen, Terho; Järvinen, Ari; Kuussaari, Mikko (Wiley-Blackwell, 2024)
To understand the potential consequences of arable land use changes for insect conservation and ecosystem functioning, it is fundamental to know how insect species with different functional traits respond to crop choice and production method.This study examined the effects of crop type and production method on functional traits of butterfly, bumblebee and carabid beetle communities using species abundance data from 78 fields in Southern Finland. Surrounding landscape composition was also accounted for. The studied traits were associated with dispersal capacity, habitat or diet specialization and phenology—the key determinants modifying species responses to agricultural disturbances and land use changes.Butterfly habitat breadth was narrowest and wingspan shortest in long-term fallows. Fallows also supported the highest share of butterflies overwintering in early development stages and bumblebees with late-emerging queens. The tongue length of bumblebees was longest in organic oat fields, probably due to flowering weeds with long corolla.For carabid beetles, the proportion of poor flyers and carnivores was highest in perennial crops and fallows. Carabid beetles overwintering as adults were relatively more abundant in organic than in conventional production, probably due to more intensive tillage in organic fields.In all insect groups, poor dispersers and/or specialists decreased with increasing arable land cover in the surrounding landscape.Increasing the area of long-term fallows and perennial crops and enhancing within-field plant diversity while maintaining landscape heterogeneity would promote insect species sensitive to agricultural disturbances and land use changes and their associated ecosystem services in boreal farmland.
Keywords: bumblebees; butterflies; carabid beetles; community-weighted means; dispersal capacity; fallows; organic production; specialization; species traits